Mehdi Chouakri Berlin : Yearbook 1999-2000. - Mehdi Chouakri, Berlin (Berlin : Mehdi Chouakri, 2000)
Fleury, Sylvie ; Bonvicini, Monica ; Bettua, Ignazio ; Armleder, John M. ; Bulloch, Angela ; Dejanov, Plamen ; Heger, Swetlana ; Fleury, Sylvie ; Rockenschaub, Gerwald ; Heimerdinger, Isabell ; Haaning, Jens ; Michel, Julien ; Monk, Jonathan ; Mercier, Mathieu
Duits
boek